PROSES BERPIKIR PESERTA DIDIK DALAM PEMECAHAN SOAL CERITA MATEMATIKA DITINJAU DARI GAYA KOGNITIF - Kabiran, Econ; Laurens, Theresia; Takaria, Johannis (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2019)
This study aims to describe the thinking process of students in solving mathematical problems of triangular and quadrilateral material in terms of cognitive style. The thinking process in this study is the steps taken by students involving mental activities in solving problems related to problem solving. The process of thinking in this study there are three kinds, namely conceptual thinking, semi-conceptual thinking and computational thinking. This research is a qualitative descriptive study. The subjects in this study were grade VII students consisting of four students with details of each two students from the Field Independent (FI) cognitive style and two students from the Field Dependent cognitive style (FD). Data collection techniques used in this study were mathematical tests and interviews. Data on the results of mathematical tests and interviews were analyzed based on indicators suitable with the conceptual thinking process, semi-conceptual thinking process and computational thinking process. From the results of data analysis, it was found that the students' thinking processes in solving mathematical story problems in the Field Independent group is the conceptual and semi-conceptual thinking processes. And students' thinking processes in solving mathematical story problems in the Field Dependent group tend to be semi-conceptual and computational thinking processes.